PENGARUH PERAN KELUARGA DAN PRAKTIKKEWIRAUSAHAAN DALAM MEMBENTUK SIKAPKEWIRAUSAHAAN MAHASISWA PENDIDIKAN EKONOMIANGKATAN TAHUN 2009-2010 FAKULTAS EKONOMIUNIVERSITAS NEGERI SURABAYA - MASITAH, DEWI (Jurnal Pendidikan Tata Niaga (JPTN), 2013)
This research aims to know is there any influence the role of the family and practices of entrepreneurship in shaping the attitudes of student entrepreneurship education Economic Force in 2009-2010 Faculty of Economics University of Surabaya. This research is quantitative. The determination of the sample with purposive of sampling techniques, where samples to be taken at 210 of respondents. The technique of the collection is done with poll. From the research is known that the role of the family and The practice of entrepreneurship influential significantly to the attitude of entrepreneurship student with an rsquare = 0,248. Which means that the magnitude of the influence of 24,8 %. Keywords: the role of the family, the practice of entrepreneurship, the attitude of entrepreneurship